The Effect of Political Participation of Chinese Citizens on Government Satisfaction: Based on Modified Causal Forest - Zhu, Meihong (Procedia computer science, 2023)
As the democratization process in China progresses, an increasing number of Chinese citizens have been participating in various political activities. This paper explores the impact of the political participation of Chinese citizens on their satisfaction with the local government (abbreviated as government satisfaction) and the possible heterogeneity of this effect across different groups. In this study, political participation is considered an intervening variable for government satisfaction. Based on data from the 2021 China Social Situation Comprehensive Survey (CSS 2021), political participation is operationalized as a three-level qualitative variable, including supportive participation, rights-defending participation, and mixed participation. The analysis shows that, on average, supportive political participants have the highest level of government satisfaction while rights-defending participants have the lowest. Furthermore, a modified causal forest model reveals that the effect of political participation varies across multiple covariates, with statistically significant heterogeneity observed in terms of citizens’ gender. In detail, the effect of females is significantly higher than that of males. However, for some specific groups, it is still worth noting, such as men, young people under the age of 27, and people with low socioeconomic status and political trust.